2008
DOI: 10.1038/sj.ejcn.1602978
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and their sociodemographic and behavioural correlates in French middle-aged adults from the SU.VI.MAX cohort

Abstract: Background/Objectives: Few studies have investigated dietary patterns among French adults. We aimed to identify dietary patterns and their relation with nutrient intakes, sociodemographic, lifestyle and other health indicators in a large population of middle-aged subjects living in France. Subjects/Methods: Dietary patterns were identified using factor analysis in 5194 women and men aged 45-60 years enrolled in the SU.VI.MAX (Supplémentation en Vitamines et Minéraux Antioxydants) study. Dietary data were based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
65
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 41 publications
20
65
3
Order By: Relevance
“…To our knowledge, up to now, no study has specifically assessed the dietary patterns of these migrant groups in France. Furthermore, in contrast with studies on the French general population (Perrin et al, 2002;Kesse-Guyot et al, 2008), an unhealthy dietary pattern among food aid users was not associated with age, marital status or education level. The influence of common sociodemographic factors seems to be lessened by differences in economic profiles and food insufficiency levels within this deprived population.…”
Section: 00contrasting
confidence: 46%
“…To our knowledge, up to now, no study has specifically assessed the dietary patterns of these migrant groups in France. Furthermore, in contrast with studies on the French general population (Perrin et al, 2002;Kesse-Guyot et al, 2008), an unhealthy dietary pattern among food aid users was not associated with age, marital status or education level. The influence of common sociodemographic factors seems to be lessened by differences in economic profiles and food insufficiency levels within this deprived population.…”
Section: 00contrasting
confidence: 46%
“…245 FSA-NPS DI was inversely associated with age in agreement with the fact that older subjects tend to 246 be more health conscious and therefore to have healthier diet. Such an observation has been 247 documented in numerous studies in Western countries [24,[39][40][41][42][43][44]. Consistent with other reports, 248 associations of risk factors, cumulating low fruit and vegetable intakes, low leisure time physical 250 activity and high alcohol consumption [45][46][47].…”
Section: Fsa-nps DI Was Not Associated With Plasma Concentrations Of supporting
confidence: 68%
“…The sociodemographic determinants of diet are well documented (16,45,(49)(50)(51)(52)(53)(54)(55) , particularly the relationship between diet and educational status (56,57) . We found that educational status is also an important predictor of dietary stability and transition.…”
Section: Study Implicationsmentioning
confidence: 99%